DEMOGRAPHIC FACTORS INFLUENCING CAREER COMMITMENT OF PROFESSIONAL COUNSELLORS IN KWARA STATE, NIGERIA - Abdulhafis Adeyinka HASSAN; Habibat Bolanle ABDULKAREEM (OPTIMA: Journal Of Guidance and Counseling, 2022)
This study investigates the demographic factors influencing the career commitment of professional counsellors in Kwara state. The main purpose of this study is to investigate demographic factors influencing the career commitment of professional counsellors in Kwara State, Nigeria. The questionnaire was used for data collection. Four hypotheses were raised and tested at a 0.05 level of significance. Data collected were analyzed using descriptive and inferential statistics at a 0.05 level of significance. The findings of the study revealed that a positive significant relationship existed between gender and career commitment (r = 3.21, p (.02) .05), age and career commitment (r = 3.64, p (.02) .05), academic qualification and career commitment (r = 3.08, p (.03) .05) and marital status and career commitment (r = 3.78, p (.02) .05). The findings of the study showed that there were significantly different between the demographic factors of (gender, age, academic qualification and marital status) and career commitment of professional counsellors in Kwara State. Based on this it was suggested that irrespective of their gender, age, academic qualification and marital status every counsellor should put forward skills and responsibility of rescuing present-day school children, as a means of doing their work diligently and committed.